PERANCANGAN SISTEM INFORMASI AKUNTANSI PERMINTAAN DANA UNTUK KEGIATAN PEMBIAYAAN PROYEK PADA PT. TIRSULA INOVASI AMBON - Ratumurun, samuel (Optimum: Jurnal Ekonomi dan Pembangunan, 2015)
Structuring the accounting information system is one of the factors thatdetermine the performance of companies in managing fi nancialtransactions andstrategic decision making process. PT. Trisula Inovasi, initially conduct f nancial transactions in the activities of the project fi nancing is only done by a director and adata entry and assisted by some force fi eld, so the greater the risk of deviations against financial documents and the accounting process, especially on the transaction project financing. This deviation can happen easily, because the absence of the document fow system of structuring financial transactions and integrated them regularly.The purpose of accounting information system design is to produce financial information to supportdaily operations, management decisions and meet obligations related to accountability and minimizing deviations to be performed by White-collar crime.